Proteomics analysis of human rabies CSF - Willoughby, R. E.; Halligan, B.; Green, A. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
The pathogenesis of human rabies is incompletely understood. Wildtype rabies infection is minimally cytolytic or inflammatory, and does not include major disruption to the blood brain barrier. Cerebrospinal fluid (CSF) from human rabies patients is therefore ideally suited for direct analysis by proteomics approaches that may substantively elucidate the immune responses, alterations in metabolism and fundamental cellular mechanism that contribute to rabies pathogenesis and recovery. We examined 20 control CSF and 13 CSF samples from 6 patients with laboratoryconfirmed rabies, dating from hospital days 4 to 59. Dog and bat rabies were equally represented. Trypsin digests of CSF proteins were analyzed by liquid reversed-phase chromatography followed by mass spectrometry using a Thermo LTQ-Orbitrap. Peptide identifications were filtered at a False Discovery Rate (FDR) of < 5% and proteins were required to have two or more peptide forms observed to be considered. No rabies virus derived peptides were detected in any sample. In aggregate, the abundance of 180 proteins were statistically significant between patients and controls (p < 0.05) when corrected for multiple testing and 36 proteins were more than 2 fold increased in patients and 64 proteins were detected only in patients only. Some of the groups that these proteins were involved in innate and acquired immunity, complement, proteases, structural proteins, synaptic granules, energy metabolism, innate immunity and natriuresis.